Scenario Planning to Guide Long-term Investments in Agricultural Science and Technology : Theory and Practice from a Case Study on India - Rajalahti, Riikka; Janssen, Willem; Pehu, Eija (World Bank, Washington, DC, 2012)
This note for India is based on the paper Scenario Planning to guide long-term investments in Agricultural Science and Technology (report no. 37066). Scenarios are an important and useful tool, providing a neutral space for discussion, and helping to build consensus among various stakeholders. The objective is to examine possible future developments that could impact individuals, organizations, or societies to find directions for decisions will most benefit any future environment. Useful in strategy formulation, scenarios can be used in policy development, conflict resolution, group learning, and rehearsing management decisions. The note analyzed results of workshops organized to define the way forward relative to the Indian Council of Agricultural Research (ICAR). The lessons learned include: (a) applying the analysis on larger, global issues may be far more challenging; (b) it is recommended the scenario process be implemented ahead of project preparation; (c) it is essential to allocate sufficient time and resources for creating client ownership and understanding; (d) it is of paramount importance to compose a multidisciplinary scenario team led by experienced scenario leaders; and (e) it is also very important to include participants of the groups the process aims to influence.